Assessment of GFR in the evaluation of potential living kidney donors at the Wits Donald Dordon Medical Center (WDGMC) and Charlotte Maxeke Johannesburg Academic Hospital (CMJAH) - Okuthe, Jacktone Odhiambo (My University, 2018)
Equations that estimate GFR (eGFR) are widely used in clinical practice to estimate kidney function in sub-Saharan Africa, but have not been validated for use in this region. This study assessed the performance of eGFR equations in adults evaluated for suitability for live kidney donation against a gold standard radionuclear GFR measurement (mGFR) and determined their usefulness for screening live kidney donors in South Africa. This study was a retrospective record review of 350 adults evaluated for living kidney donation from 1996 – 2013 at Charlotte Maxeke Johannesburg Academic Hospital (CMJAH) and Wits Donald Gordon Medical Centre (WDGMC). Their eGFR was calculated using CG, 4-v MDRD and CKD-EPI equations. Plasma clearance of 51Cr-EDTA was used as a reference method for mGFR. The 4-v MDRD (with and without ethnicity adjustment) and the CKD-EPI (without ethnicity adjustment) equations underestimated the mGFR (negative bias of -8 mL/min/1.73m2, -16 mL/min/-1.73m2 and -6.4 mL/min/1.73m2 respectively).However, the bias associated with the average mGFR using the CG and CKD-EPI (with ethnicity adjustment) equations was not significant (2.3 mL/min/1.73m2 and 0.6 respectively).Use of the ethnicity factor resulted in overestimation of mGFR for both the 4v-MDRD equation (by 24.2ml/min/1.73m2 compared to 6.8 ml/min/1.73m2 without it) and the CKD-EPI equation (by 21.8ml/min/1.73m2, compared to 7.6ml/min/1.73m2, without the ethnicity factor). In conclusion, this study showed that almost half of adults screened for living donation in Johannesburg were not eligible due to comorbid hypertension, diabetes and unexplained kidney disease. In addition, the error statistics worsened as mGFR increased and all four prediction equations had a low sensitivity for determining individuals with a GFR <80 ml/min/1.73m2. Based on the findings in this study, use of a gold standard measured GFR should be the preferred method for assessing kidney function in potential living kidney donors in South Africa.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Medicine Johannesburg, 2018.
Keywords: Kidney Donors